Prevalence of bacterial uropathogens and their antimicrobial susceptibility patterns among pregnant women in Eastern Ethiopia: hospital-based cross-sectional study - Alemseged Workneh Ejerssa; Diriba Alemayehu Gadisa; Teferra Abula Orjino (BMC, 2021)
Abstract Background Urinary tract infection (UTI) is the commonest bacterial infections during pregnancy, leading to significant maternal and prenatal morbidity and mortality. Method This hospital-based cross-sectional study during November 2017 to January 2018 was aimed to determine hospital-based antibacterial susceptibility patterns of bacterial uropathogens among 200 pregnant women in Eastern Ethiopia. ~ 10-20 ml clean-catch midstream urine samples were collected by the study participants. The well-mixed urine samples standardized to 1 µl have inoculated onto Cystine Lactose Electrolyte-Deficient and MacConkey agar. The inoculum was cultured at 37 °C under aerobic conditions for 18-48 h and examined macroscopically to evaluate the colony appearance and size of colonies. The isolate on the plates with pure growth and colonies ≥ 105 CFU/ml were further subjected to biochemical identification and susceptibility testing according to the standard procedures explained in the Clinical and Laboratory Standards Institute guideline. SPSS version 25 was used for data analysis. Descriptive statistics such as frequency, percentage, and cross-tabulation were used to present the findings in the form of graphs and tables. Results The response rate for this study was 98.04%. Thirty-one bacteria were isolated among the 200 urine samples processed, which gave the overall UTI prevalence of 15.5%. The majority (90.3%) of the isolates were Gram-negative. Escherichia coli (45.2%) was the most frequent isolated uropathogen which followed by Proteus spp. (22.6%), Klebsiella pneumoniae (16.1%), Staphylococcus aureus (9.7%), and Pseudomonas aeruginosa (6.5%). Among the isolates, 96.4% of them were susceptible to amikacin and followed by nitrofurantoin (90.3%), and gentamicin (83.9%). However, high rates of resistance to ampicillin (58.1%), amoxicillin-clavulanate (51.6%), and cotrimoxazole (51.6%) were observed. Overall, 16(51.6%) of the bacterial isolates had developed multiple drug resistance to the selected antimicrobials. Conclusion In general, the overall prevalence of UTI was high, 15.5%. Most of isolated bacterial uropathogens were Gram-negative bacteria, and Escherichia coli was the most frequent isolate. The majority of the isolates were susceptible to amikacin, nitrofurantoin, and gentamicin. However, a high rate of resistance was observed to ampicillin, amoxicillin-clavulanate, and cotrimoxazole. More than half of the isolated bacteria had multiple drug-resistant features. Therefore, periodic and continuous urine culture for screening and diagnosis is mandatory to reduce the consequence of UTI and multidrug resistance bacteria in pregnancy.